A novel approach for efficient fabrication of chitosan nanoparticles-embedded bacterial nanocellulose conduits. (15th July 2021) - Wei, Zhao; Pan, Pan; Hong, Feng F.; Cao, Zhangjun; Ji, Ying; Chen, Lin
Graphical abstract: Highlights: The three-dimensional fibril network of BNC was used as a physical dispersionphase. Chitosan nanoparticles-embedded BNC conduits were efficiently fabricated using ionic gelation method. Correlations of performance of CSNPs-BNC conduits with CS concentration were investigated. Antibacterial activity and biocompatibility of the conduits were evaluated in vitro and in vivo . CSNPs-BNC composite is a kind of potent biomaterial in biomedical applications. Abstract: Incorporation of chitosan (CS) into Bacterial nanocellulose (BNC) matrix is of great interests in biomedical field due to the advantageous properties of each material. However, the conventional strategies result in poor composite effect with low efficiency. In this study, the three-dimensional fibrillar network of BNC was utilized as a template for the first time to homogeneously disperse CS to form nanoparticles (CSNPs) in BNC matrix via ionic gelation method, to develop chitosan nanoparticles-embedded bacterial nanocellulose (CSNPs-BNC) composites. This composite method is simple and efficient, without introducing dispersants and crosslinking agents, while retaining the mechanical properties and native 3D network structure of BNC. The CSNPs-BNC composites had excellent antibacterial activity to support potential clinical application. The CSNPs-BNC composites could promote the adhesion and proliferation of Schwann cells, and demonstrate good biocompatibility both in vitro and in vivo . The results indicated that CSNPs-BNC can provide a promising candidate for biomedical applications.